IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DALAM PENINGKATAN MUTU PENDIDIKAN DI SMA NEGERI 1 RAMAN UTARA KABUPATEN LAMPUNG TIMUR - Jumari, Jumari (Lembaga Penelitian UM Metro, 2017)
School-Based Management is a management where the school is an important decision-making unit on the provision of education independently, by providing greater control opportunities for schools for education in their respective schools. With the implementation of School Based Management (MBS), making schools more independent in managing schools, and can create school creativity by utilizing resources, resources, and learning resources available to improve the quality of education in schools. The goal in this research are: (1) To describe the implementation of MBS in SMA Negeri 1 Raman Utara East Lampung regency. (2) To describe the obstacles in the implementation of MBS in improving the quality of education in SMA Negeri 1 Raman Utara East Lampung Regency. (3) To describe which is done in overcoming obstacles in the implementation of MBS in SMA Negeri 1 Raman Utara East Lampung regency. This research was conducted at SMA Negeri 1 Raman Utara East Lampung regency on May 3, 2017 until May 27, 2017. This research uses qualitative research approach with field research. As for the subject of research as a source of data is the principal, Vice principal in the field of infrastructure facilities, teachers, and school treasurer. Using interview and observation data collection technique. And analyzed by using triangulation method. From the research results can be concluded that the implementation of school-based management implemented by the head of SMAN 1 Raman Utara is the Management of teacher empowerment, Management of school infrastructure, and Management of education funds.